The detailed palaeoecology of a mid-Wisconsinan interstadial (ca. 32 000 (14)C a BP) vegetation surface from interior Alaska - Wooller, Matthew J.; Zazula, Grant D.; Blinnikov, Misha; Gaglioti, Benjamin V.; Bigelow, Nancy H.; Sanborn, Paul; Kuzmina, Svetlana; La Farge, Catherine (Journal of Quaternary Science, 2011)
We present a multi-proxy reconstruction from a well-preserved vegetation surface (ca. 32 000 (14)C a BP) from the Fox Permafrost tunnel near Fairbanks, Alaska. A thick litter layer of plant material on the vegetation surface is consistent with the vegetation lacking evidence of disturbance. Plant macrofossils and graminoid cuticle analysis show the presence of a graminoid assemblage consistent with phytolith data. The pollen data indicate that trees were not local to the site and that Artemisia sp. was present in the region. The insect and bryophyte reconstructions are consistent with the vascular plant reconstruction, indicating the site was at least periodically wet. delta(13)C values from the graminoids present show a large range encompassing both the wet and dry range displayed by modern graminoids in Alaska. Sequential delta(13)C analyses conducted along the length of leaves attached to the vegetation surface indicate a seasonal shift towards relatively higher water use efficiency. The lower water use efficiency earlier in the growing season may have stemmed from the use of winter season meltwater by plants at the site - a scenario consistent with the site's cryostratigraphy. Our multi-proxy reconstruction contributes to the limited palaeoecological data available for graminoid-dominated vegetation present in Eastern Beringia and particularly the interior of Alaska during the mid-Wisconsinan interstadial. Copyright (C) 2011 John Wiley & Sons, Ltd.
id: 2131; PT: J; TC: 1; UT: WOS:000296091300010

Late Pleistocene paleoecology of arctic ground squirrel (Urocitellus parryii) caches and nests from Interior Alaska's mammoth steppe ecosystem, USA - Gaglioti, Benjamin V.; Barnes, Brian M.; Zazula, Grant D.; Beaudoin, Alwynne B.; Wooller, Matthew J. (Quaternary Research, 2011)
Botanical analyses of fossil and modern arctic ground squirrel (Urocitellus parryii) caches and nests have been used to reconstruct the past vegetation from some parts of Beringia, but such archives are understudied in Alaska. Five modern and four fossil samples from arctic ground squirrel caches and nests provide information on late Pleistocene vegetation in Eastern Beringia. Modern arctic ground squirrel caches from Alaska's arctic tundra were dominated by willow and grass leaves and grass seeds and bearberries, which were widespread in the local vegetation as confirmed by vegetation surveys. Late Pleistocene caches from Interior Alaska were primarily composed of steppe and dry tundra graminoid and herb seeds. Graminoid cuticle analysis of fossil leaves identified Calamagrostis canadensis, Koeleria sp. and Carex albonigra as being common in the fossil samples. Stable carbon isotopes analysis of these graminoid specimens indicated that plants using the C(3) photosynthetic pathways were present and functioning with medium to high water-use efficiency. Fossil plant taxa and environments from ground squirrel caches in Alaska are similar to other macrofossil assemblages from the Yukon Territory, which supports the existence of a widespread mammoth steppe ecosystem type in Eastern Beringia that persisted throughout much of the late Pleistocene. (C) Published by Elsevier Inc. on behalf of University of Washington.
id: 2130; PT: J; TC: 0; UT: WOS:000296672100009